A Note on Methods for Vertical Accuracy Assessment of DEMs - Quesada Quesada, Marvin Elí (2017)
This study investigates the vertical accuracy of a DEMs interpolated from 1:50,000 contours with universal kriging (UK) using DEMs interpolated from 1:10,000 contours as the independent source of higher accuracy following the geospatial accuracy standards proposed by the Federal Geographic Data Committee, FGDC, (1998). In accordance with the standards, the 1:10,000 contours do not qualify as well-defined points with known horizontal position and a high degree of accuracy that are easily visible and recoverable on the ground. Hence, DEMs are created from the 1:10,000 contours and used to check the vertical accuracy of the 1:50,000 DEMs with elevation errors, an RMSE and vertical accuracy measure calculated between the 1:10,000 and 1:50,000 DEMs. Other methods of vertical accuracy assessment for the 1:50,000 DEMs include a comparison of elevation ranges, visualization of error surfaces and latitudinal and longitudinal terrain profiles.